Modern space-time variations of the index of continentality and the amplitude of a seasonal course of the surfase air temperature on the territory of Ukraine - Boychenko, S.G.; Voloshchuk, V.M.; Serdiuchenko, N.N. (Reports of the National Academy of Sciences of Ukraine, 2017)
The paper analyzes the features of the space-time variations of Gorczynski and Johanson—Ringleb continentality indices and the amplitude of a seasonal course of the surface air temperature in Ukraine under the conditions of modern global warming. It is found that, against the background of a general decrease in the continentality indices and the amplitude of seasonal temperature variations on the territory of Ukraine during the period 1900—2015, there is a rapid increase in their values in the last 45 years, which is associated with an increase in the frequency of anomally high temperatures in summer. It is suggested that, in accordance with the earlier hypothesis proposed by us, this is the result of a shift of the northern periphery of the belt of subtropical anticyclones, including the territory of Ukraine.